Propuesta para el diseño de un kit de estacionamiento para bicicletas en viviendas con espacios reducidos (2019)
The present work of degree is developed from evidencing several space needs that currently have housing, with bicycles and their complementary elements being the focus where through industrial design a solution is proposed optimizing the reduced places where bicycles are parked inside a housing unit.